Autophagy induction by thiostrepton improves the efficacy of immunogenic chemotherapy. Issue 1 (26th March 2020) - Wang, Yan; Xie, Wei; Humeau, Juliette; Chen, Guo; Liu, Peng; Pol, Jonathan; Zhang, Zhen; Kepp, Oliver; Kroemer, Guido
Abstract : Background: Immunogenic cell death (ICD) is a peculiar modality of cellular demise that elicits adaptive immune responses and triggers T cell-dependent immunity. Methods: Fluorescent biosensors were employed for an unbiased drug screen approach aiming at the identification of ICD enhancers. Results: Here, we discovered thiostrepton as an enhancer of ICD able to boost chemotherapy-induced ATP release, calreticulin exposure and high-mobility group box 1 exodus. Moreover, thiostrepton enhanced anticancer immune responses of oxaliplatin (OXA) in vivo in immunocompetent mice, yet failed to do so in immunodeficient animals. Consistently, thiostrepton combined with OXA altered the ratio of cytotoxic T lymphocytes to regulatory T cells, thus overcoming immunosuppression and reinstating anticancer immunosurveillance. Conclusion: Altogether, these results indicate that thiostrepton can be advantageously combined with chemotherapy to enhance anticancer immunogenicity.